2015
DOI: 10.1007/s11661-015-3010-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving the High-Cycle Fatigue Lives of Fe-30Mn-0.9C Twinning-Induced Plasticity Steel Through Pre-straining

Abstract: The tensile properties, high-cycle fatigue properties, and microstructure evolutions during fatigue process of asreceived and pre-strained Fe-30Mn-0.9C twinning-induced plasticity (TWIP) steel were investigated. It is found that the fatigue lives of the TWIP steel can be effectively improved through pre-straining, since the deformation twins induced by pre-straining could effectively lead to the improved yield strength and the homogenized deformation. This study may provide possible ways for improving the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 27 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Considering the dispersion of the fatigue experimental data, the average life is used to fit. The fitted equations are shown as below: where σ a is the stress amplitude; N f is the number of cycles to failure; σf' is fatigue strength coefficient, which is cyclic stress corresponding to N f = 1; b is the fatigue strength exponent, which is the slope of the S–N curve and controlled by the specific damage mechanism (Wang et al., 2015, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the dispersion of the fatigue experimental data, the average life is used to fit. The fitted equations are shown as below: where σ a is the stress amplitude; N f is the number of cycles to failure; σf' is fatigue strength coefficient, which is cyclic stress corresponding to N f = 1; b is the fatigue strength exponent, which is the slope of the S–N curve and controlled by the specific damage mechanism (Wang et al., 2015, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…where a is the stress amplitude; N f is the number of cycles to failure; 0 f is fatigue strength coefficient, which is cyclic stress corresponding to N f ¼ 1; b is the fatigue strength exponent, which is the slope of the S-N curve and controlled by the specific damage mechanism (Wang et al, 2015.…”
Section: S-n Curves Of Conventional Specimen and Simulation Partmentioning
confidence: 99%
“…Substantial references have been published focusing on the mechanisms of cold work/pre-straining on the LCF behaviours of ASS, aluminium and magnesium alloy [13][14][15][16][17], among which CL Zhou et al [18,19] investigate the effects of prior tensile plastic deformation on the torsional fatigue properties of a structural steel. As for the DSS, however, the researchers are mainly concerned with the effects of pre-straining/cold-work on the basic mechanical properties, microstructural evolution during monotonic loadings [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that TWIP steels exhibit a fatigue limit (FL) close to the yield stress (YS) [7,8,11,12], which is not superior compared to other steel grades [13,14]. Both prestraining [8,15,16] or grain refinement [12,14] have been proved to be effective strategies to increase the fatigue strength. During cyclic loading, TWIP steels may display cyclic hardening and/or cyclic softening depending on the initial microstructure and applied stress/strain amplitude [8][9][10]16].…”
Section: Introductionmentioning
confidence: 99%
“…Microstructure evolution during fatigue of TWIP steels has been investigated in only a few studies [8,10,15,16]. The occurrence of deformation twinning under cyclic loading is not yet clarified due to the contradictory experimental evidences reported in the literature.…”
Section: Introductionmentioning
confidence: 99%